Non-farm economy and rural development - Mehta G S (New Delhi Anmol, 2003)
This book deals with various issues related to the structure of growth, factors influencing to the expansion, contribution in creating employment and income opportunities and problems existing in the proper functioning of different non-farm activities. I
Keywords: India; Rural conditions; Rural development; Rural poor; Uttarakhand (India); Uttaranchal